2006
DOI: 10.1109/tvlsi.2006.878263
|View full text |Cite
|
Sign up to set email alerts
|

"It's a small world after all": NoC performance optimization via long-range link insertion

Abstract: Networks-on-chip (NoCs) represent a promising solution to complex on-chip communication problems. The NoC communication architectures considered so far are based on either completely regular or fully customized topologies. In this paper, we present a methodology to automatically synthesize an architecture which is neither regular nor fully customized. Instead, the communication architecture we propose is a superposition of a few long-range links and a standard mesh network. The few application-specific long-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
172
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(173 citation statements)
references
References 41 publications
1
172
0
Order By: Relevance
“…Moreover, for arbitrary network sizes, randomized networks can be generated with the smaller computational costs than the optimized networks. These topologies can improve bandwidth, scalability, and fault-tolerance for both HPC networks [3]- [5] and on-chip networks [23].…”
Section: Low-latency Random Topologies For Hpc Systemsmentioning
confidence: 99%
“…Moreover, for arbitrary network sizes, randomized networks can be generated with the smaller computational costs than the optimized networks. These topologies can improve bandwidth, scalability, and fault-tolerance for both HPC networks [3]- [5] and on-chip networks [23].…”
Section: Low-latency Random Topologies For Hpc Systemsmentioning
confidence: 99%
“…2-D mesh topology is one of the most practical and extensively used network topologies [31][32][33][34][35] because of its regularity, simple addressing scheme, and multiple source-destination routes [31]. In this mode, packets are divided into flits, which are the smallest unit of flow control and are equal to the network channel width, excluding flit headers, as shown in Fig.…”
Section: Noc-based Test Platformmentioning
confidence: 99%
“…Ogras et al [44] showed that a significant reduction in the average packet latency can be achieved by superposing a few long-range links to a standard mesh network. In their approach, the links are however not inserted at random but where they are most useful.…”
Section: B Addressing Interconnect Challenges Bymentioning
confidence: 99%
“…The different system sizes we used were: (1) N = S = [9,14,19,24,29,34,39,44,49,54,59,64] for random multitudes, (2) N = S = [9, 16, 25, 36, 49, 64, 81, 100, 121] for 2D CAs, and (3) N = S = [8,27,64,125] for 3D CAs. Shortest path routing was used.…”
Section: A Experiments 1: System Scalabilitymentioning
confidence: 99%